Relationship between night-sleep duration and risk for depression among middle-aged and older people: A dose–response meta-analysis - Li, Xin-lin; Wei, Jiayin; Zhang, Xinying; Meng, Zhuo; Zhu, Wentao (Frontiers in Physiology, 2023)
Objective: The study aimed to examine the dose–response associations between night-sleep duration and depression risk in middle-aged and older adults. Methods: We searched PubMed, Embase, Web of Science, CNKI, VIP, and the Wanfang data knowledge service platforms from inception to 31 July 2022. Cohort and case–control studies assessing the relationship between night-sleep duration and depression were selected. We used the Newcastle–Ottawa scale to assess the quality of the published research. Two researchers carried out data extraction and quality assessment. The restricted cubic spline function and generalized least squares method were used to establish dose–response relationships between sleep duration and depression. We aimed to analyze the estimated effect size presented as the risk ratio (RR) and its 95% confidence interval (CI) using Stata 12.0. Result: Six cohort studies with 33,595 participants were included in this meta-analysis. A U-shaped association between sleep duration and depression risk was revealed. On one hand, compared with 7-h of night sleep, both shorter and longer sleep duration were associated with an increased risk of depression (5 h: risk ratio = 1.09, 95% confidence interval = 1.07–1.12; 6 h: RR = 1.03, 95% CI = 1.02–1.04; 8 h: RR = 1.10, 95% CI = 1.05–1.15; 9 h: RR = 1.31, 95% CI = 1.17–1.47; 10 h: RR = 1.59, 95% CI = 1.31–1.92; non-linear test p < 0.05). On the other hand, an increased risk of depression with shorter sleep duration was observed in middle-aged and older people among the non-Asian population (5 h: RR = 1.09; 95% CI = 1.02–1.17), while both shorter and longer sleep duration can increase the risk of depression among an Asian population (5 h: RR = 1.10, 95% CI = 1.07–1.13; 6 h: RR = 1.04, 95% CI = 1.02–1.05; 8 h: RR = 1.09, 95% CI = 1.05–1.14; 9 h: RR = 1.35, 95% CI = 1.18–1.53; 10 h: RR = 1.70, 95% CI = 1.36–2.12). Conclusion: The lowest-risk onset of depression occurred among middle-aged and older people with 7 h of night sleep, which suggested that shorter and longer night-sleep duration might lead to an increased incidence of depression. Clinical Trial Registration:https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=344052, identifier 344052